Intensified extraction and stripping of uranium using membrane dispersion microextractor - Zheng Wei; Xiao Ge; Hui Wang; Zhongwei Yuan; Taihong Yan; Weifang Zheng (Results in Engineering, 2024)
The extraction and stripping of uranium(VI) using membrane dispersion microextractor were investigated in high phase ratio. The effects of residence time, aqueous phase flowrates and organic phase flowrates, as well as nitric acid and the extractant concentration on the stage efficiency were evaluated. With the increase of aqueous phase flowrate and organic phase, the efficiency firstly decreased and then increased. Both the extraction efficiency and stripping efficiency can reach >90 % at high phase ratio within 10 s. The efficiency decreased with the increase of nitric acid in aqueous phase, whereas the efficiency increased with the increase of tributyl phosphate (TBP) concentration. Finally, mass transfer characteristic in extraction process in membrane dispersion microextractor was discussed. The overall mass transfer coefﬁcient in membrane dispersion microextractor could reach 0.13 s−1 at A:O = 5:1 and 0.058 s−1at high A:O ratio of 40:1.